Enhancing Student Engagement Through Extracurricular Activities. - HOCHSTEIN, LISA H.; COLCLOUGH-DAVY, ROBINA K. (Clinical Laboratory Science)
St. Johns University's clinical laboratory sciences curriculum is a 3 + 1 program. New freshman and transfer students are introduced to the major during their first year in an "Introduction to Clinical Laboratory Sciences" course. This course has a "shadowing" component as part of the course requirement along with lecturematerial. The laboratory visits last 1--2 hours and are conducted by senior students at their rotation sites. After completion of the course, students are not seen in class again for 2 years. During these 2 years, students do not engage with other students in their program. Clinical laboratory science is a small major, and the size makes it difficult to identify other students in the major. The programalso does not offer social and professional support and resources for students before their professional year. To keep students engaged and to allow them to meet other students from their major, the Clinical Laboratory Sciences Association has been organized. This group holds monthlymeetings during the activity hour. A chapter of the Lambda Tau honor society has also been created. New members are inducted in the spring semester of the junior year, duringmedical laboratory professionalsweek. Lastly, a White Coat Convocation is held to welcome senior students into their professional year. This ceremony is held just prior to the beginning of the students' clinical rotations. By adding these activities, the students are engaged and excited to begin their professional year of study. Based on the first year, in which all of these extracurricular activities were used, the students have become a more unified group throughout the different classes.